Library selections and recommendations of native mobile applications - Arroyo-Vázquez, Natalia (Anuario ThinkEPI, 2014)
Libraries have traditionally selected and recommended books, music, and movies. Mobile apps can also be readily included, thus extending library services by offering users more content, resources and services in different formats. Some basic ideas to tackle the discovery, selection and recommendation of native mobile apps are addressed in this text. Processes, information sources, selection criteria to be take ninto account, and what information to provide to the users are also defined.